REVIEW OF COMMUNITY EMPOWERMENT AND YOUTH INTEREST IN MOSQUES: FOCUS ON MANAGING AND IMPROVING SERVICE QUALITY - Jaya, Fanlia Prima (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
This study aims to find things that influence the empowerment of people and the interest of adolescents in mosques, as well as how mosque management can contribute to improving the quality of services so that adolescents are more involved in activities in mosques. The population in this study is all mosques in Banjarmasin City, which is 207 mosques. The sample is drawn from 100 Jami Mosques spread across Banjarmasin City, with the analysis unit of Takmir Masjid, Remaja Masjid, and Community in the Mosque environment in Banjarmasin City. The analysis uses the Partial Least Square model with t-tests with the following results, Mosque Management has a significant effect on Community Empowerment and Youth Interest in Mosques in Banjarmasin City; Mosque Management does not have a significant effect on Service Quality in Mosques in Banjarmasin City, Mosque Management has a significant effect on Service Quality through Community Empowerment in Mosques in Banjarmasin City, Mosque Management has a significant effect on Quality Service through Youth Interest in Mosques in Banjarmasin City. Keywords: Community Empowerment, Youth Interest, Mosque Management, Quality of Service